Why decentralize decision making? English local actors' viewpoints. Issue 1 (2nd October 2018) - Richardson, Liz; Durose, Catherine; Dean, Rikki J.
Abstract : Decentralized decision making has created restructuring from larger to smaller administrative units, but in many places, strays little from existing arrangements. Moves toward decentralization from central government to city‐regions, and in some areas, below city‐region scale to neighborhoods, reflect a mandate for reform. What is the nature and extent of desired reforms? Using an institutionalist lens, homogeneity and heterogeneity in local narratives about possible future reform can be surfaced. This article emphasizes the importance of understanding the role of local actors' narratives in shaping decentralized institutions. This article uses the findings from a Q‐methodology study to identify and interrogate distinctive local viewpoints on attempts to decentralize decision making in England. In a systematic empirical analysis, local actors' narratives were largely in favor of relatively minor modifications to the status quo. The findings question a conflation of decentralization with participation in decision making.